New insights into ternary geometrical models for material design - Zhigang Yu; Haiyan Leng; Qun Luo; Jieyu Zhang; Xiaochun Wu; Kuo-Chih Chou (Materials & Design, 2020)
Geometrical model is an important part of the CALPHAD method and has been widely used for the prediction of physicochemical properties of multicomponent systems. However, most of the researches are focused on the comparison of the predicted results by various geometrical models, and very few studies have analyzed the underlying causes of these differences. In this paper, we will discuss the factors affecting the predicted results of geometrical models by analyzing the whole calculation procedures. When the experimental data is constant, it is found that the predicted results are mainly affected by two factors, which can be concluded as the fitting order of Redlich-Kister equation and the selection rules of three representative points. The influences of the two factors are analyzed in the viscosity prediction of Au-Cu-Ag ternary system.